Once again smile curve: Is chain upgrading possible? - Yanikkaya, Halit; Altun, Abdullah; Tat, Pinar (Wiley, 2023)
The geographic fragmentation of the production process inevitably leads to the question of whether or not there is a relationship between the level of value-added and the position of production stages along with a global production/value chain, known as the smile curve as the theoretical literature suggests. This study investigates the relationship between value-added and production stages across more than 34 sectors over 40 countries for two different periods, 1995-2011 and 2000-2014, by taking into account a variety of different measures of production stage and country-sector heterogeneity. In the first step, we utilize the decomposition methodology of Wang, Wei, Yu, and Zhu (2017) to track the production stages across country sector. In the second step, we test our hypotheses by employing the fixed effects (FE) estimation technique. The results show that the relationship between value-added content in output and backward length exhibits a U-shaped distributional pattern. The significant results for both developed and developing economies indicate the potential of economies to benefit from the functional upgrading along with production stages. Our general conclusion regarding production chains is also valid for stages mainly related to the global value chain (GVC), especially for developed countries. Furthermore, capital intensity and total factor productivity appear to be crucial factors for improvements in process upgrading. Given the robust and positive impacts of chain upgrading in all countries considering both the total production process and GVC part, industries should exploit the opportunities for higher value-added in the global production system.
Keywords: backward production lengths; GVCs; sectoral value-added content; smile curve